The glass kingdom : a novel - Osborne, Lawrence, 1958- (Hogarth, 2020)
"Leaving New York for the heat, humidity and anonymity of Bangkok, Sarah arrives in Thailand with the sole desire to lose herself, a stranger in a strange land. Yet she also leaves behind a complicated past, and a deception she holds close to her chest. Taking up a lease at a high-end apartment complex called The Kingdom, she finds herself drawn into the close-knit social circle of three very different, but equally mysterious, ex-pat women: Ximena, the Chilean chef, creator of fine and delicious culinary creations; Nat, the British hotelier with the curious husband and even more curious maid; and the alluring Mali, who takes Sarah into her glittering world with all its shadow-play. As attempted coups wrack the city and political chaos erupts on the streets below, so do tensions within the gilded world of the compound. When a tenant in the building goes missing, and the disorder of the outside world begins to invade The Kingdom, the residents are thrown into unprecedented terror and suspicion. The question Sarah must now ask herself is: Who can she trust? The Kingdom is a brilliantly unsettling story of civil and psychological unrest, fate and karma, in the furthest reaches of the world and in the human psyche"--